Decades of Recovery From Sheep Grazing Reveal No Effects on Plant Diversity Patterns Within Icelandic Tundra Landscapes - Mörsdorf, Martin A.; Ravolainen, Virve T.; Yoccoz, Nigel G.; Thórhallsdóttir, Thóra Ellen; Jónsdóttir, Ingibjörg Svala (Frontiers in Ecology and Evolution, 2021)
Tundra plant communities are often shaped by topography. Contrasting wind exposure, slopes of different inclination and landforms of different curvature affect habitat conditions and shape plant diversity patterns. The majority of tundra is also grazed by ungulates, which may alter topographically induced plant diversity patterns, but such effects may depend on the spatial scales of assessments. Here we ask whether topographically induced patterns of within (alpha) and between (beta) plant community diversity are different in contrasting grazing regimes. We studied plant communities within tundra landscapes that were located in the North and Northwest of Iceland. Half of the studied landscapes were grazed by sheep, whereas the other half was currently un-grazed and recovering for several decades (up to 60 years). Alpha and beta diversity were assessed on explicitly defined, nested spatial scales, which were determined by topographical units. Although we contrasted currently grazed vegetation to vegetation that witnessed several decades of grazing recovery, we found no statistically significant differences in plant diversity patterns. We relate these findings to the low resilience of our study system toward grazing disturbances, which has important implications for management practices in the tundra. Effects of topography on species richness were only found for specific spatial scales of analyses. Species rich topographical units were associated with relatively large biomass of plant growth forms that promote nutrient availability and potential plant productivity in the tundra, such as forbs. This suggests that biomass of such plant growth forms within habitats can be a useful proxy of potential plant productivity and may predict spatial patterns of plant species richness in tundra.